Does Türkiye Have a Demographic Dividend? NUTS 2 Analysis - Seda Ertürk; Selçuk Koç (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
As the population in Turkey continues to age, the share of the working-age population in the total population has also started to decline. However, the fact that the share of the working-age population is at most 2/3 while the country's population is ageing may occur a demographic window of opportunity and a demographic dividend for economic growth. In this study, the demographic dividend for 2023-2050 in NUTS 2 regions of Turkey with different fertility rates is calculated by projection analysis. According to the results of the study, it is estimated that Turkey entered the demographic dividend process in 2023 and may peak in 2036-2037. This trend is expected to persist until 2050. An analysis of NUTS 2 regions suggests that certain areas, such as TR31 (İzmir) and TR62 (Adana-Mersin), are projected to achieve the highest demographic dividend. This trend is expected to persist until 2050. An analysis of NUTS 2 regions suggests that certain areas, such as TR31 (İzmir) and TR62 (Adana-Mersin), are projected to achieve the highest demographic dividend. This trend is expected to persist until 2050. An analysis of NUTS 2 regions suggests that certain areas, such as TR31 (İzmir) and TR62 (Adana-Mersin), are projected to achieve the highest demographic dividend.